2011
DOI: 10.1590/s1808-86942011000500012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of glucocorticoids on nasal polyps

Abstract: Glucocorticoids are considered the main treatment option for nasal polyps, but their effect is only recently being understood. Aim To evaluate whether fluticasone propionate (FP) inhibits the inflammatory process induced by TNF-alpha in vitro , and to assess if NF-kappaB is associated to this inhibition. Study Design Experimental in vitro study. Materials and Methods Nasal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…This finding may be due to the therapeutic control being different between both patient groups, and as a consequence, the inflammation biomarkers are controlled in AERD; this result has been reported by Baraket et al, who demonstrated a decrease in TNF-α concentrations in a bronchioalveolar wash after treatment with inhaled fluticasone propionate in asthmatic patients [32]. Varela et al reported a similar finding in cultivating fibroblasts from nasal polyps, which, upon exposure to this steroid, inhibit the synthesis of cellular adhesion molecules [33]. In a similar model, Silvestri et al reported a decrease in the expression of ICAM-1, but not VCAM-1, in the presence of TNF-α [34].…”
Section: Discussionsupporting
confidence: 55%
“…This finding may be due to the therapeutic control being different between both patient groups, and as a consequence, the inflammation biomarkers are controlled in AERD; this result has been reported by Baraket et al, who demonstrated a decrease in TNF-α concentrations in a bronchioalveolar wash after treatment with inhaled fluticasone propionate in asthmatic patients [32]. Varela et al reported a similar finding in cultivating fibroblasts from nasal polyps, which, upon exposure to this steroid, inhibit the synthesis of cellular adhesion molecules [33]. In a similar model, Silvestri et al reported a decrease in the expression of ICAM-1, but not VCAM-1, in the presence of TNF-α [34].…”
Section: Discussionsupporting
confidence: 55%
“…The final effect of GC on nasal diseases is the inhibition of pro-inflammatory cytokines (IL-1 , TNF-, GM-CSF, IL-3, IL-5, IL-6), chemokines (IL-8, RANTES, eotaxin) and adhesion molecules (VCAM-1, ICAM-1) [1, 13,42]. Glucocorticoids also have a favorable effect on tissue remodeling (reducing MMP expression) [43,44], reduce mucin production [45], increase cell apoptosis [46,47], and decrease mast cell recruitment and activation [48].…”
Section: Glucocorticoid Action On Nasal Mucosamentioning
confidence: 99%
“…Similar to immune cells, studies have suggested that fibroblasts might utilize TLRs for sense pathogens, resulting in the production of many mediators contributing to the control of the infection [8,9]. Gingival fibroblasts constitutively express TLR2, TLR3, and TLR4 [10], and also the adhesion molecules ICAM-1 (CD54) and CD44 [11,12]. Activation of gingival fibroblast with microbial products induced the production of proinflammatory cytokines [13,14].…”
Section: Introductionmentioning
confidence: 99%